Socially responsible internal communication? Analysing the combined effect of CSR and internal communication on employees' affective bond to organization - Gomes, Daniel (2018)
Positive organizational differentiation between competitors is a critical matter for every organization in current economic scenarios. This “La Palisse” truth is obviously related to the fact that organizations deal with extreme difficulties in what regards valid ways of developing themselves with efficiency and with efficacy, as a natural consequence of integrating widespread competitiveness-based economies. In addition, current economic crisis scenario (notably in the European Union) has brought severe challenges to organizations, which have sped up the necessity of quality, innovation, organizational change or business ethics (e.g. Gomes, Asseiro & Ribeiro, 2013). Internal Communication (IC) is a strategic management area that directly deals with the internal publics of organizations (their workers). IC strategy follows the approach that information within an organization is a relevant resource, in such way, that its proper use when accompanied by inclusion actions regarding the internal publics brings them a relevant sense of awareness (D’Almeida & Libart, 2000). Curiously, this idea of vigilance and of the building of a supportive organization towards its human resources is also present in Corporate Social Responsibility’s (CSR) guidelines (e.g. Neves & Bento, 2005). When discussing CSR and its contributions for management, we become immediately alerted to the prospects of understanding its impact on effective IC management practices, notably on the employee-organization relationship improvement issues. In this matter, the existing literature is consistent in associating to both areas, directly or indirectly, several interesting contributions regarding critical indicators of individual performance at work, such as commitment, awareness or satisfaction (e.g. Brault, 1992; Brammer, Millington, & Rayton, 2007). However, despite of the amount of theoretical reasoning accumulated over the years regarding the importance of IC and CSR, these two areas still linger to be associated with the prediction of relevant individual indicators in joint models of analysis, such as employee commitment. Following these considerations, and using a quantitative methodology, this study’s main purpose is to investigate how employees’ affective commitment can be predicted by IC (considering its different axis), and evaluating if Internal CSR’s orientations play a significant contextual role in this relationship. As such, we propose that Internal CSR’s orientations will have a moderating influence on the positive association between the IC’s axis and employee affective commitment, as we are expecting CSR to strengthen the IC-Commitment relation. With this model of analysis, we will be able to evaluate if Socially Responsible IC brings an added-value to employee commitment purposes. In this sense, the present study aims to explore an answer to the following question: do Internal CSR’s guidelines moderate the relationship between IC and employees’ affective commitment?